Enhancing Teachers Scientific Writing Proficiency through Effective Coaching Clinic Implementation: A Case Study at MA Salafiyah Bode Plumbon, Cirebon - Yudi Yanto, Eko (AIM: Journal of Islamic Education Management, 2023)
The primary objective of this research is to enhance the proficiency of teachers at MA Salafiyah Bode Plumbon, Cirebon, in the composition of scientific papers. Employing the Action Research methodology as developed by Kemmis & McTaggart, the study encompasses four integral stages: planning, acting, observing, and reflecting. Over the course of two cycles, a cohort of 16 teachers at MA Salafiyah Bode Plumbon, Cirebon, actively participate as the subjects of this research. The data collection methodology comprises various techniques, including observation, tests, and questionnaires, with a specific focus on extracting information related to the outcomes and processes of the coaching clinic. The research findings signify that the implementation of the coaching clinic significantly enhances the adeptness of teachers in crafting scientific papers. This conclusion is substantiated by the achieved average scores and the percentage of mastery. Observations during the coaching clinic sessions vividly illustrate the progressive improvement in teachersâ€™ capabilities to articulate scientific content effectively. In the initial cycle, the average score for the ability to write scientific papers stands at 73.75, with a corresponding mastery rate of 50%. Advancing to the subsequent cycle, there is a notable increase in the average score to 84.81, coupled with a commendable mastery rate of 100%. Consequently, the application of the coaching clinic emerges as an efficacious strategy in augmenting the proficiency of teachers in scientific paper composition at MA Salafiyah Bode Plumbon, Cirebon. Â Â